Digital Communication Strategy Of Generation Z In Food Waste Management To Achieve SDGs In Ruang Pangan Lampung Community - Annisa Ghina Istighfarany; Tina Kartika; Nina Yudha Aryanti; Andy Corry Wardhani (INJECT (Interdisciplinary Journal of Communication), 2025)
Generation Z in the Ruang Pangan community, based in Lampung, plays an important role in achieving the Sustainable Development Goals (SDGs), particularly through reducing food waste and managing food surpluses. This research aims to analyze the communication strategies implemented by Generation Z to promote food sustainability initiatives. Using a descriptive qualitative approach and the Diffusion of Innovation theory, this study shows how the community strategically uses digital and participatory communication channels to raise awareness and stimulate behavior change. Their actions exemplify the role of youth-led initiatives in supporting SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption), and SDG 13 (Climate Action) through food rescue programs and educational campaigns. The results show that Generation Z, through Ruang Pangan, effectively succeeded in raising public awareness on sustainable food management and acted as agents of change in achieving the SDGs. In addition, there are changes in community behavior through digital media and cross-sector collaboration, such as initiatives and innovations in food rescue and collection. Ruang Pangan educates and campaigns for food management as a communication strategy carried out both offline and online. And the findings show that Generation Z can serve as early adopters and agents of change in sustainable development, and highlight the potential for program replication in other regions with local customization.